2019
DOI: 10.1002/cjce.23615
|View full text |Cite
|
Sign up to set email alerts
|

The effects of modes of hydrogen input and reactor configuration on reaction rate and H2 efficiency in the catalytic hydrogenation of alkynol to alkenol

Abstract: Hydrogenation often involves three phases where hydrogen‐on‐demand is the typical mode of operation in industrial scale reactors. In research labs and publications, however, continuous hydrogen flow has been used. This paper investigates the effect of such modes of operation on reaction rate using a selective hydrogenation of 3‐butyn‐2‐ol over Pd/Al2O3 to obtain 3‐buten‐2‐ol as the model reaction. The two modes of operation were first tested in a commercial PARR stirred tank reactor and then repeated in an osc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The use of a pulsed baffled tube photochemical reactor has been demonstrated for three-phase heterogeneous catalysed photo-reactions and has shown good performance due to the effective solid handling capacity of this reactor type Skelton, 2000, 1999). Navarro-Fuentes et al (2019b carried out catalytic hydrogenation of alkynol to alkenol in an OBR and found that due to the enhanced multiphase mixing and mass transfer, the OBR consumes five times less power, provides more than two times higher 𝐻𝐻 2 efficiency and 50% lower residence time to achieve the same reaction performance obtained in a commercial STR.…”
Section: Gas-liquid-solid Systemsmentioning
confidence: 99%
“…The use of a pulsed baffled tube photochemical reactor has been demonstrated for three-phase heterogeneous catalysed photo-reactions and has shown good performance due to the effective solid handling capacity of this reactor type Skelton, 2000, 1999). Navarro-Fuentes et al (2019b carried out catalytic hydrogenation of alkynol to alkenol in an OBR and found that due to the enhanced multiphase mixing and mass transfer, the OBR consumes five times less power, provides more than two times higher 𝐻𝐻 2 efficiency and 50% lower residence time to achieve the same reaction performance obtained in a commercial STR.…”
Section: Gas-liquid-solid Systemsmentioning
confidence: 99%
“…The existing literature on alkynol hydrogenation has focused on tertiary alkynols, notably 2-methyl-3-butyn-2-ol . The only reported transformation of secondary alkynols involved liquid-phase conversion of 3-butyn-2-ol using Pd/Al 2 O 3 in pressurized (oscillatory baffled vs stirred tank) reactors. , We have recently reported the formation of 2-butanol and 2-butanone as by-products in the continuous hydrogenation of 3-butyn-2-ol over a commercial Pd/Al 2 O 3 catalyst . Four possible reaction pathways are associated with the hydrogenation of 3-butyn-2-ol, as shown in Figure .…”
Section: Introductionmentioning
confidence: 99%
“…Pd NPs supported by oxides with hierarchical porosities and special functional groups have also been widely applied in the semi-hydrogenation of alkynols to enols [38][39][40][41][42][43][44][45][46][47][48][49][50]. The formation of interfaces between Pd NPs and oxide supports and the introduction of organic groups allow one to tune the adsorption of substrates and intermediates on the catalyst surface and thus realize chemoselective hydrogenation.…”
Section: Monometallic Pd Catalystsmentioning
confidence: 99%